Translanguaging pelas brechas: práticas de letramento crítico-decolonial em tempos pandêmicos - Phelippe Nathaniel Ribeiro Oliveira (2023)
As a Critical Applied Linguistics research project that aims to reflect upon the relationship between language education and social issues, this study is developed at and for a time of multiple and interconnected crises (BUTLER, 2022). Drawing on theoretical and methodological assumptions of the translinguistic turn (LEE; DOVCHIN, 2020) and the epistemologies of the South, this dissertation discusses, from a praxiological perspective, literacy practices informed by the Decolonial Turn (MALDONADO-TORRES, 2011, MIGNOLO, 2018) and critical literacies (DURRANT; GREEN, 2000; LANKSHEAR; SNYDER; GREEN, 2000; MATTOS, 2011, 2015). The translanguaging scholarship, as a research paradigm, offers ontological and epistemological bases for the construction of linguistic knowledge that is detached from the notions and ideologies engendered by and for modernity, such as the very monolingual orientation (CANAGARAJAH, 2013), still deeply rooted in language learning-teaching in Brazil. By means of a transmethod Action Research Project (MCNIFF; WHITEHEAD, 2010), which mobilizes principles from autoethnography (ADAMS; ELLIS; JONES, 2016; KRESS, 2010) and Narrative Inquiry (BARKHUIZEN; BENSON; CHIK, 2014; NACARATO, 2018; PASSEGGI, 2018) in a transversal and transdisciplinary manner, this study sought to explore the concrete opportunities created by the translingual orientation, here understood as curricular cracks (DUBOC, 2012), for critical-decolonial literacy practices at a Brazilian federal public school. Such practices allowed the identification, problematization and destabilization of the discourses engendered by the modernity/coloniality pair, as well as the development of critical thinking that uncovers and overcomes the permanent state of crises produced and managed by neoliberalism at the present.